2016
DOI: 10.1590/2175-7860201667302
|View full text |Cite
|
Sign up to set email alerts
|

Composição florística das epífitas vasculares em duas fisionomias vegetais no município de Botucatu, estado de São Paulo, Brasil

Abstract: ResumoEm fragmentos de Floresta Paludosa (FP) e Floresta Estacional Semidecídua (FES), em Botucatu, São Paulo (22º 55'23"S e 48º 27'28"W), através de expedições mensais no período de um ano, foi avaliada a composição florística das epífitas vasculares, classificadas de acordo com as categorias ecológicas e síndromes de dispersão. Foram realizadas comparações das similaridades florísticas com outras florestas também com clima sazonal. As coletas foram depositadas no Herbário Rioclarense (HRCB), depois de identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…The altitude can justify these results, whereas that richest areas in vascular epiphytes have been recorded in elevations between 1,000 and 2,000 m in several studies (Madison 1977;Gentry & Dodson 1987;Benzing 1990;Küper et al 2004;Krömer et al 2005; The richest families are according to the patterns found in the Neotropical Region (NR) (Mendieta-Leiva et al 2020) and the Atlantic Forest (AF) (Ramos et al 2019), in which Orchidaceae and Bromeliaceae are the richest. Polypodiaceae is the third richest family and often occupy such rank in small scales, although Araceae, the third in AF and NR, is the fourth richest family in the SR (Hietz & Hietz-Seifert 1995;Wolf & Alejandro 2003;Obermüller et al 2012;Marcusso & Monteiro 2016;Furtado & Menini Neto 2018a;Araújo et al 2019;Barbosa et al 2019), which was corroborated in the present study. These four families together represent 70% of the recorded species in the SR.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The altitude can justify these results, whereas that richest areas in vascular epiphytes have been recorded in elevations between 1,000 and 2,000 m in several studies (Madison 1977;Gentry & Dodson 1987;Benzing 1990;Küper et al 2004;Krömer et al 2005; The richest families are according to the patterns found in the Neotropical Region (NR) (Mendieta-Leiva et al 2020) and the Atlantic Forest (AF) (Ramos et al 2019), in which Orchidaceae and Bromeliaceae are the richest. Polypodiaceae is the third richest family and often occupy such rank in small scales, although Araceae, the third in AF and NR, is the fourth richest family in the SR (Hietz & Hietz-Seifert 1995;Wolf & Alejandro 2003;Obermüller et al 2012;Marcusso & Monteiro 2016;Furtado & Menini Neto 2018a;Araújo et al 2019;Barbosa et al 2019), which was corroborated in the present study. These four families together represent 70% of the recorded species in the SR.…”
Section: Resultssupporting
confidence: 88%
“…Thus, in addition to watercourses, the RPPNABV is above 1,000 m a.s.l. and is influenced by orographic rainfalls, and can therefore offer favorable conditions for species demanding a moister environment (Bonnet et al 2010;Marcusso & Monteiro 2016), as the species occurring in the rainforest, such as Asplenium mourai, Cirrhaea dependens, Cochlidium punctatum, Elaphoglossum glaziovii, Epidendrum chlorinum, Hymenophyllum caudiculatum, Lellingeria apiculata, Melpomene pilosissima, Moranopteris achilleifolia, Phlegmariurus biformis, P. fontinaloides, Vriesea bituminosa, V. longicaulis, and V. penduliflora. (BFG 2018) and are not present in the RBRG, which has lower elevations between ~500 and 700 m a.s.l.…”
Section: Resultsmentioning
confidence: 99%
“…The predominance of holoepiphyte characteristics is an expected pattern (Freitas et al 2016;Zotz 2016). On the other hand, the great number of facultative holoepiphytes recorded is outstanding (38.1 % overall) when compared with some sites of the Atlantic Forest (Bonnet et al 2011;Padilha et al 2015;Couto et al 2016;Marcusso & Monteiro 2016;Rolim et al 2016). This different pattern could be explained by the abundance of rock outcrops in the studied area (Biral & Lombardi 2012;Perleberg et al 2013;Couto et al 2016).…”
Section: Discussionmentioning
confidence: 97%